Influences of Patriarchal Culture and Femicide as a Form of Gender-based Violence against Women from Human Rights Perspective - Refikal, Fanny (Salasika, 2024)
A patriarchal culture is a form of normalization of violent crimes committed by men against women. Patriarchal culture itself is a wrong assumption because cultural elements are everything that can be inherited from one generation to another. However, Patriarchy, which is the oppression of women and should not be used as a culture to be inherited, still exists and is justified in society so that there is a gender gap between men and women. The phenomenon of femicide that occur in Indonesia is the influence of patriarchal culture and gender inequality, where there is social inequality towards the culture and status of women in the community. Currently, patriarchal culture is still in the midst of society and patriarchal culture itself is considered normal. However, patriarchal culture gave birth to femicide with rampant killings on the basis of grudges and hatred by men against women. Before the occurrence of femicide, the perpetrator first often persecutes the victim, such as those of rape, sexual harassment, domestic violence, coercion or restraint. The rise of the phenomenon of femicide in Indonesia is proof of the weak law enforcement in Indonesia and the carelessness of public attention to women and girls in their own country. Femicide is a violent crime committed with an element of awareness by the perpetrator who ends up killing the victim. It is a gender-based human rights violation.